Google rules : the history and future of copyright under the influence of Google - Gray, Joanne Elizabeth (Oxford scholarship online., 2020)
'Google Rules' traces the rise of Google through its legal, commercial and political negotiations over copyright. Today, Google reigns over an order that features empowered private companies and rapidly changing conditions. The book explores Google's accumulation of power over the past two decades and the implications for the public interest.